2016
DOI: 10.1016/j.cell.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effector T Cells Abrogate Stroma-Mediated Chemoresistance in Ovarian Cancer

Abstract: SUMMARY Effector T cells and fibroblasts are major components in the tumor microenvironment. The means through which these cellular interactions affect chemoresistance is unclear. Here, we show that fibroblasts diminish nuclear accumulation of platinum in ovarian cancer cells, resulting in resistance to platinum-based chemotherapy. We demonstrate that glutathione and cysteine released by fibroblasts contribute to this resistance. CD8+ T cells abolish the resistance by altering glutathione and cystine metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
292
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(324 citation statements)
references
References 32 publications
8
292
0
2
Order By: Relevance
“…These results, taken together with the recent report by Wang et al 13 indicating the stromal-derived glutathione in chemotherapy resistance, 13 point to molecular mechanisms regulating redox states in cancer cells and their effect on cancer progression and chemotherapy resistance.…”
supporting
confidence: 67%
“…These results, taken together with the recent report by Wang et al 13 indicating the stromal-derived glutathione in chemotherapy resistance, 13 point to molecular mechanisms regulating redox states in cancer cells and their effect on cancer progression and chemotherapy resistance.…”
supporting
confidence: 67%
“…Human peripheral blood T cells were stimulated for 5 days with anti-CD3 and anti-CD28 in the presence of IFN-γ-activated DCs, macrophages, or fixed primary ovarian cancer cells (41,42). Antihuman PD-L1 and isotype controls were added at the beginning of culture (26).…”
Section: Discussionmentioning
confidence: 99%
“…27 It was recently shown that CD8 + T cellYderived INF-F controls fibroblast glutathione and cysteine via the JAK/STAT1 pathway, diminishing nuclear accumulation of platinum in ovarian cancer cells. 28 Studies on signal transduction pathways and the key role of molecular markers that are related to resistance/sensitivity to chemotherapy in ovarian epithelial tumor are crucial. Gene expression is regulated by cytokines that control the immune response in tumor tissue.…”
Section: Resultsmentioning
confidence: 99%